Pengaruh Transformational Leadership Terhadap Innovation Pada Prodi Manajemen Pemasyarakatan Politeknik Ilmu Pemasyarakatan - Asriza Purba; Padmono Wibowo (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Transformational leadership has been recognized as an important influencer in the innovation system of various industries. Educational institutions survive by changing leadership skills to manage their knowledge resources efficiently and increase the ability to innovate teaching and learning towards study programs. Therefore, the purpose of this study was to investigate whether there is a relationship between transformational leadership and innovation in correctional management study program. The study involved a survey of 100 cadets from the Correctional Management Study Program at the Correctional Science Polytechnic. Questionnaires were distributed using the media google form and then the data was processed using SPSS 27. Based on the results of the research, transformational leadership had a positive and significant effect on innovation in Correctional Management Study Program, Polytechnic of Correctional Sciences with a coefficient of determination of 0.707 or 70.7%.